2020
DOI: 10.1111/ggr.12312
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Halite Fluid Inclusions as an Accurate Palaeothermometer: Brillouin Thermometry Versus Microthermometry

Abstract: Halite traps inclusions of the mother fluid when precipitating. When unchanged, the density of these fluid inclusions (FIs) records the water temperature T f at the time of crystal formation. As halite is ubiquitous on Earth and geological time, its FIs possess a high potential as temperature archives. However, the use of FIs in halite as an accurate palaeothermometer has been hampered due to limitations of microthermometry, the most commonly used analytical method. Here, we show how Brillouin spectroscopy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…0.7). To select suitable FIs for analysis, published criteria for accurate Brillouin analysis on halite crystals (Guillerm et al, 2020) was followed. For palaeothermometry, the previously described full set‐up and detailed physical principles of BS were used (El Mekki‐Azouzi et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…0.7). To select suitable FIs for analysis, published criteria for accurate Brillouin analysis on halite crystals (Guillerm et al, 2020) was followed. For palaeothermometry, the previously described full set‐up and detailed physical principles of BS were used (El Mekki‐Azouzi et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…During their formation, NaCl crystals may trap droplets of the surrounding lake water from which they precipitate, called fluid inclusions (FIs). Recently, a new palaeothermometer based on Brillouin spectroscopy (BS) was elaborated on FIs in natural quartz (El Mekki‐Azouzi et al, 2015) and laboratory‐grown NaCl crystals (Guillerm et al, 2020), and used on a sedimentary core from the DSB to reconstruct temperature and lake‐level changes of the Dead Sea over the Last Interglacial (LIG, 130–115 ka; Guillerm, 2019). In the present contribution, the focus is on a shorter time interval encompassing three closely spaced samples, to reconstruct palaeotemperature variability of the lake waters at an unprecedented (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in a detailed study of synthetic and natural NaCl crystals grown at a known temperature, Lowenstein et al [74] have shown that T h obtained after cold treatment have erratic values, biased towards low temperatures. This is likely due to irreversible deformation of the fluid inclusion during the temperature cycle [75]. Lowenstein that only a fraction of the inclusions show a bubble after cooling.…”
Section: The Problem With Evaporitesmentioning
confidence: 99%
“…The liquid pressure is still lower than P ∞ when the bubble is present, but this has a negligible effect on sound velocity. Using synthetic halite samples with known synthesis temperature, this technique was shown to be superior to microthermometry 28 , and it was applied to natural samples deposited in the Dead Sea basin during the last interglacial 43 .…”
Section: And Perspectivesmentioning
confidence: 99%
“…This is problematic in the field of geosciences, where T h of fluid inclusions in minerals is used to determine the fluid density and gain insight on the conditions at which the inclusion was formed 25 . For instance, T h in inclusions formed near the Earth's surface in salt crystals (halite) [26][27][28] or in speleothems made of calcite in caves 29 serve for reconstructing past temperatures. This motivated Marti et al 21 to develop their thermodynamic model and propose (for pure water) a procedure to correct the observed T h and recover T ∞ h , which they applied to speleothems 30 .…”
Section: Introductionmentioning
confidence: 99%